Perceptual and motor performance of combat-sport athletes differs according to specific demands of the discipline - Wei-Ying C.; Wu, S. K.; Tai-Fen, S.; Kuei-Ming, C.; Kuei-Yuan, W.; Yao-Ching, C.; Goodbourn, P. T. (Perceptual and Motor Skills, 2017)
The specific demands of a combat-sport discipline may be reflected in the perceptual-motor performance of its athletes. Taekwondo, which emphasizes kicking, might require faster perceptual processing to compensate for longer latencies to initiate lower-limb movements and to give rapid visual feedback for dynamic postural control, while Karate, which emphasizes both striking with the hands and kicking, might require exceptional eye-hand coordination and fast perceptual processing. In samples of 38 Taekwondo athletes (16 females, 22 males; mean age =19.9 years, SD = 1.2), 24 Karate athletes (9 females, 15 males; mean age=18.9 years, SD = 0.9), and 35 Nonathletes (20 females, 15 males; mean age = 20.6 years, SD = 1.5), we measured eye-hand coordination with the Finger-Nose-Finger task, and both perceptual-processing speed and attentional control with the Covert Orienting of Visual Attention (COVAT) task. Eye-hand coordination was significantly better for Karate athletes than for Taekwondo athletes and Nonathletes, but reaction times for the upper extremities in the COVAT task-indicative of perceptual-processing speed--were faster for Taekwondo athletes than for Karate athletes and Nonathletes. In addition, we found no significant difference among groups in attentional control, as indexed by the reaction-time cost of an invalid cue in the COVAT task. The results suggest that athletes in different combat sports exhibit distinct profiles of perceptual-motor performance. ABSTRACT FROM AUTHOR